The politics of aesthetics : the distribution of the sensible - Rancière, Jacques (London ; New York : Continuum, 2006)
Translator's Introduction: Jacques Ranciere's Politics of Perception; THE POLITICS OF AESTHETICS; Foreword; The Distribution of the Sensible: Politics and Aesthetics; Artistic Regimes and the Shortcomings of the Notion of Modernity; Mechanical Arts and the Promotion of the Anonymous; Is History a Form of Fiction?; On Art and Work; A New Interview with Jacques Ranciere for the English Edition: The Janus-Face of Politicized Art; Historical and Hermeneutic Methodology; Universality, Historicity, Equality; Positive Contradiction; Politicized Art; Afterword by Slavoj Zizek: The Lesson of Ranciere
Includes bibliographical references (p. [94]-101) and index.
boek